Bibliometric analysis and visualization of Connexin 43 in the field of solid tumor research(2000-2024) - Huang, Caiqi; Liu, Xiaoman; Feng, Yanhui; Xiao, Zhesi; Lu, Zhengjia; Wang, Lu; Ming, Jia (Frontiers in Immunology, 2025)
BackgroundConnexin 43 (Cx43) plays a pivotal role in tumor growth, metastasis, and disease progression. This study employs bibliometric analysis to identify key research trends and emerging hotspots in Cx43-related solid tumor research.MethodsIn December 2024, the Web of Science Core Collection (WoSCC) database was searched for publications on Cx43 in solid tumor research from 2000 to 2024. Bibliometric analysis and data visualization were primarily conducted using CiteSpace, VOSviewer, and Bibliometrix, with a focus on visualizing aspects such as countries, institutions, journals, authors, references, and keywords in the field.ResultsA total of 1,666 publications were retrieved, with the annual number of articles and citations continuing to grow. The United States and China had the highest number of publications, while the University of Western Ontario in Canada was the leading institution, with the most publications by Christian C.G. Nau. Lampe, P.D. was the most cited author. The International Journal of Molecular Sciences was the most frequently published journal, and the Journal of Biological Chemistry was the most frequently co-cited journal. High-frequency keywords included phosphorylation, breast cancer, gastric cancer, prognostic markers, anti-tumor immune response, and drug resistance.ConclusionContemporary research focuses on the role of Cx43 phosphorylation in tumorigenesis, progression, and metastasis, its potential as a prognostic biomarker, and its critical role as an immunotherapeutic target and in tumor drug resistance. These studies provide a comprehensive analysis for a deeper understanding of the role of Cx43 in solid tumors and help to promote further research in this area.